Young learners' use of social media for information seeking : exploring core LIS journals from 2010-2014 - Hyldegård, Jette (2021)
Background. Increased use of social media for information seeking and learning calls for more research and knowledge of how these emerging technologies can support students’ learning. Objectives. The focus is on recent studies of young learners’ use of social media for information seeking in an academic context. Methods. The research is based on critical reading of core library and information science (LIS) journals and a selected number of conference proceedings spanning 2010 to 2014. The examination of the selected journals and proceedings was guided by two general questions: 1) Which information seeking activities, strategies and preferences can be identified when young learners use social media for information seeking in relation to course work and other study-related work tasks? 2) What motivations can be identified among young learners for using social media for information seeking in a study context? Results. Seven studies were identified and reviewed. According to the reported results, use of social media tends to afford certain types of behavior. Specific strategies, tactics and criteria were used when requesting and evaluating information or formulating information needs. The reported factors motivating information seeking were convenience and easy access to information, in addition to the content associated with specific social media types. Students’ use of social media for information seeking was associated primarily with their private information landscape. Contributions. The challenges of using non-traditional social sources for information seeking identified in the studies raise questions of how teachers and information professionals can educate young learners to use social media competently as information seekers and authors of information.